Sistem Tataniaga Tandan Buah Segar (TBS) Kelapa Sawit (Studi Kasus di Desa Tegar, Kecamatan Mandau, Kabupaten Bengkalis, Provinsi Riau) - ANDIKA, ANDIKA; AMBARAWATI, I GUSTI AGUNG AYU; SETIAWAN, I GEDE BAGUS DERA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.11, No.1, Juli 2022, 2022)
Fresh Oil Palm Bunches Trading System (Case Study of Tegar Village, Mandau District, Bengkalis Regency, Riau Province).  Oil palm is one of the leading commodities in Mandau District with a total production of 812,927.8 tons. Unfortunately, this large production has not been facilitated by an efficient trading system, especially when viewed from the benefits received by farmers in Tegar Village. This study aims to analyze the trading system, trading channels and trading costs, as well as the share margin received by each of the trading channels of fresh oil palm bunches in Tegar Village, Mandau District, Bengkalis Regency. 30 farmer respondents were selected using purposive sampling technique. Using qualitative and quantitative analysis, this study shows that the trading system of fresh oil palm bunches in Tegar Village is a one channel trading pattern, in which farmers sell to intermediary traders, who then transport the fresh oil palm bunches to palm oil processing factories. The trading system analysis result shows that the margin value in this channel is 14.23%, with farmer's share of 85.77%, and a profit ratio of 43.60%. Operationally this channel is an efficient channel.